PEMBERDAYAAN MASYARAKAT DALAM PEMETAAN DAN OPTIMALIASI POTENSI DESA WISATA SEGAJIH LIVE IN EDUCATION KULON PROGO - Yoga Yoga Sahria; Septiono Eko Bawono (LPPM Universitas Abdurrab, 2023)
Desa Wisata (Desa Wisata) Segajih is located in Hargotirto, Kulon Progo, Yogyakarta, Indonesia. The village is known for its stunning natural beauty, such as green hills, waterfalls, rivers, and vast rice fields. In addition, in Segajih Tourism Village there are also several homestays / inns and serve regional specialties. Segajih Tourism Village carries the concept of